The demonstration of a herpesvirus, related to bovine herpesvirus 1, in reindeer with ulcerative and necrotizing lesions of the upper alimentary tract and nose - Rockborn, G.; Rehbinder, C.; Klingeborn, B.; Leffler, M.; Klintevall, K.; Nikkilä, T.; Landén, A.; Nordkvist, M. (Rangifer, 1990)
In 11 male reindeer, all esposed to transportation stress, signs of conjunctivitis and later on ulcerative and necrotizing lesions of the mucosa of the nostrils and mouth were recorded. Blood and secretions from the nose were sampled. Antibodies to bovine herpesvirus 1 (BHV-1) were detected in 2 animals. No animal had antibodies to bovine viral diarrhoea virus (BVDV). Virus isolation was negative. The sampling was repeated 2 weeks later and complemented with biopsies from the mouth lesions, fixed in formalin. At this occasion 3 animals were seropositive to BHV-1 and in biopsies from 2 of these intranuclear herpesvirus-like particles were found by means of electron microscopy. Four animals, 3 of them seropositive, were treated with cortison during 8 days. The size of the ulcers in the mouth increased in all animals. A herpesvirus was isolated from 3 of them at 10 different occasions. The ultrastructural investigation of the virus suspension demonstrated the presence of typical herpesvirus particles. On day 11 all 4 animals suffered from a severe diarrhoea and anorexia. On day 12 one animal died and on day 13 post challenge with cortison two additional animals died. The remaining animal was slaughtered on day 13. Bacteriological investigation revealed growth of Fusobacterium necrophorum from the spleen and oral wounds of all 4 animals. The animals were obviously subjected to an infection with a herpesvirus colsely related to BHV-1. Virus could be liberated by cortison treatment. It is possible that infections with the found herpesvirus, and the lesions caused by it, may be the background to earlier recorded severe outbreaks of necrobacillosis of the alimentary tract in reindeer herds.